Relationship among change of direction performance, muscular power and sprint speed in female and male elite soccer players - Hirose, N. (Journal of Athletic Enhancement, 2020)
We aimed to identify useful parameters to develop an effective fitness training strategy for senior female soccer players. Hence, we examined the change of direction performance (CODp), sprint speed, muscular power, and anthropometric data among female soccer players, and compared the findings with those from similar tests applied in male soccer players. Thirty-three female and forty male soccer players from the top Japanese league were examined. The differences between elite vs. sub-elite players and playing position were assessed, and simple correlation coefficients between motor performance and anthropomorphic parameters were analyzed. As a result, elite male and female players had better CODp and muscular power than sub-elite players. Elite male players had higher sprint speed than sub-elite players (p<0.01), regardless of position. However, in female players, the sprint speed was dependent on position. A large difference in the effect size for sprint speed was observed between female forwards (FW) and midfielders (MF) (d=0.85) and defenders (DF) (d=1.00) (FW<MF/DF). The CODp was correlated with sprint speed (r=0.62 for female; r=0.54 for male, p<0.01) and muscular power (r=-0.54, p<0.01; r=-0.50, p<0.05). These results indicate that the absence of a gender difference in the correlation coefficients among CODp, muscular power, and sprint speed, suggesting that the training strategy should be depend on a player`s motor ability level rather than on gender in senior top-level soccer players